Promises and Challenges of Perovskite Solar Cells: A Comprehensive Review - Ashif Mohammad; Farhana Mahjabeen (BULLET : Jurnal Multidisiplin Ilmu, 2023)
A promising photovoltaic technology with great efficiency, affordable production, and promise for many uses has emerged: perovskite solar cells. With a focus on five key areas—device architectures and fabrication methods, efficiency enhancements, stability and durability concerns, environmental impacts and sustainability considerations, commercialization and market potential—this paper offers an overview of the benefits and drawbacks of perovskite solar cells. Alternative topologies and scalable production approaches are explored in the section on device architectures and fabrication techniques for perovskite solar cells. Perovskite solar cell efficiency improvements are reviewed in terms of new perovskite compositions, light control methods, and tandem structures. Research on more stable perovskite materials, encapsulating methods, and a knowledge of degradation mechanisms are used to address stability and durability issues. Perovskite solar cells' effects on the environment and sustainability issues are investigated, with a focus on lead toxicity and resource usage during manufacturing. The development of lead-free materials, improved production techniques, life cycle analyses, and recycling promotion are all highlighted. Scalability, dependability, cost competitiveness, and market acceptance are highlighted as being essential for the successful deployment of perovskite solar cells in the commercialization and market potential section. Perovskite solar cells are incorporated into many applications, and future prospects and research initiatives are also addressed. The current state of perovskite solar cell technology is thoroughly reviewed in this paper, along with the major difficulties and potential future research areas. The results help to clarify the benefits and drawbacks of perovskite solar cells and offer insightful information for researchers, business people, and politicians engaged in the creation and application of this potential renewable energy technology.